2016
DOI: 10.1089/omi.2016.0148
|View full text |Cite
|
Sign up to set email alerts
|

To Genotype or Phenotype for Personalized Medicine? CYP450 Drug Metabolizing Enzyme Genotype–Phenotype Concordance and Discordance in the Ecuadorian Population

Abstract: Genetic variations within the cytochrome P450 (CYP450) superfamily of drug metabolizing enzymes confer substantial person-to-person and between-population differences in pharmacokinetics, and by extension, highly variable clinical effects of medicines. In this context, "personalized medicine," "precision medicine," and "stratified medicine" are related concepts attributed to what is essentially targeted therapeutics and companion diagnostics, aimed at improving safety and effectiveness of health interventions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…The present study supports this hypothesis by showing no differences in plasma levels of drugs in the different phenotypes. Another clinical study showed, that a proportion of healthy individuals with a PM genotype are phenotypically EMs as measured by CEIBA metabolization ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study supports this hypothesis by showing no differences in plasma levels of drugs in the different phenotypes. Another clinical study showed, that a proportion of healthy individuals with a PM genotype are phenotypically EMs as measured by CEIBA metabolization ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, CYP2D6 genotype-phenotype matching alone may not produce a desirable result, as studies have reported discordance in genotype-predicted PMs [5456], and recent studies also suggested that CYP2D6 genotype was not a good predictor of ultra rapid metabolism[18, 19, 57]. Gaedigk et al[58], and Zineh et al[59], have proposed an Activity Score (AS) that are calculated from the CYP2D6 gene and use to determine the CYP2D6 metabolic activities of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CYP2D6 phenotypes varies among different populations and races: studies showed 7– 10% PMs among Caucasians [14, 15], 1–2% PMs in the Asian populations [16, 17], 6.9% PMs in the Cuban populations [18], 3.1% PMs in the Ecuadorian populations[19], and 1–4% PMs population in Africa [20–23]. In Nigeria, few available studies among the many ethnic populations indicate a prevalence of PMs of 0–3.5% [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…The global aim of this work was to assess the usefulness of the CEIBA cocktail in the nonclinical evaluation of metabolic-based drug interactions in Wistar rats, as it was originally designed and utilised to measure the specific-metabolic activity of CYP isoenzymes (CYP1A2, CYP2C9, CYP2C19, CYP2D6 and CYP3A4) in humans (41). Several important differences between human and rat CYP isoenzymes involved in the metabolism of the four probe drugs of the CEIBA cocktail were previously confirmed, as shown in Table 3 (26,(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%